Comment faire du neuf avec du vieux : le Métadictionnaire médical multilingue, une nouvelle phase de la bibliothèque numérique Medica - Jean-François Vincent (Humanités Numériques)
The Multilingual Medical Metadictionary of the Medica digital library (Université Paris Cité) was designed as part of a Collex-Persée call for projects, in line with Medica’s documentary policy. As the mass digitisation of the first decades of the 21st century has produced considerable results, digital libraries are now expected to produce more sophisticated services, such as this one. The Metadictionary should be useful not only to linguists, but also to Medica’s other audiences. It should enable users to query its entire corpus of dictionaries. It enriches the existing corpus of the oldest dictionaries in the medical field, and adds Greek searching. It provides a list of the entries in the corpus. By structuring the articles of seven dictionaries, it exploits translations and other links between words and phrases to enable enriched circulation within the corpus. All these links are easy to verify.